Ethical Development of Professional Image in Professional Codes of Engineering Ethics - Wajszczyk, Piotr (Annales. Etyka w Życiu Gospodarczym, 2014)
The article discusses problems of image development in selected professional engineering communities, as expressed in their ethical codes. Specific codified norms are presented and their likely effects discussed on two levels: personal and social.The findings show, that not all of the codes of ethics solve the development problem identically, with the differences likely to cause some variability in be-havioural patterns among members of the professional societies.The analysis suggests the need for further research and analyses as well as the standardization of codified solutions to this problem among professional engineering societies.